KONSTRUKSI FRASA ADJEKTIVAL DALAM MAJALAH TEMPO 2022: â€œDARI UTARA MEMBELA KAUM HAWAâ€ - Yulfiha Nur Azizah; Haryadi Haryadi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
The purpose of this research is to (1) describe the types of adjective phrases, (2) describe the categories of attribute filling words in adjectival phrases, and (3) describe the syntactic function of adjektival phrases in the Special Report of Tempo Magazine, Sunday, December 25, 2022, entitled â€œDari Utara Membela Kaum Hawaâ€. The research approach used is a qualitative descriptive and syntactic approach. The method of collecting data is through the listening method with advanced techniques, free engagement-free viewing, and note-taking techniques. Meanwhile, the data analysis method used is the Direct Element Division method with advanced techniques in the form of dissipation techniques, expansion techniques, and reverse techniques. The results of data analysis are presented through an informal presentation method. The results showed that 35 data of adjective phrases were divided into 17 endocentric adjective phrases and 18 exocentric adjective phrases. The types of adjective phrases found based on the number of cores consist of (1) attributive endocentric adjective phrases and (2) coordinative endocentric adjective phrases. The categories of filler words in adjective phrases are divided into (1) verbs, (2) adverbs, (3) nouns, and (4) pronouns. The adjective phrases found occupy several syntactic functions, namely (1) subject, (2) predicate, (3) object, (4) complement, and (5) adverb.